Локалізовані та нелокальні форми коливань двох пов'язаних маятників - Сурганова, Юлія Едуардівна; Міхлін, Юрій Володимирович; Кириллова, Наталія Олександрівна (Ліра, 2022)
Розглянуто форми коливань системи, що складається з двох маятників, пов'язаних пружною пружиною, причому маси цих маятників істотно розрізняються. Локалізовані і нелокальні (пов'язані) форми коливань отримано за допомогою методу малого параметра. Числове моделювання, що включає побудову фазових портретів і траєкторій в конфігураційному просторі, дозволяє оцінити стійкість отриманих форм коливань.

The oscillation modes of a system consisting of two pendulums connected by an elastic spring are considered, and the masses of these pendulums differ significantly. Localized and non-local (linked) modes are constructed using the small parameter method. Numerical modeling, which includes the construction of phase portraits and trajectories in the configuration space, allows us to estimate the stability of the obtained waveforms.
Localized and non–local vibration modes of two connected pendulums
Keywords: пов'язані маятники; нелінійні нормальні форми коливань; асимптотичні методи; стійкість; coupled pendulums; nonlinear normal modes of oscillations; asymptotic methods; stability